The Effects of Inaccurate Blood Sample Volume on Prothrombin Time (PT) and Activated Partial Thromboplastin Time (aPTT) - Peterson, Powers; Gottfried, Eugene L (Thrombosis and Haemostasis, 1982)
The results of determinations of the prothrombin time (PT) and the activated partial thromboplastin time (aPTT) are frequently used to assess hemostatic function. Accurate results for these laboratory tests depend on many variables, one of which is the ratio of plasma to anticoagulant. We studied 12 patients and 4 normal subjects to determine the effects of sample volume on PT and aPTT. We conclude that underfilling may produce profound effects, particularly on the aPTT. In contrast, overfilling rarely affects the results. The greatest effects of sample volume were observed in specimens in which the true PT or aPTT was elevated. A normal PT or aPTT result on any specimen, regardless of sample volume, strongly suggests that the true value is normal.
Keywords: Prothrombin time; Activated partial thromboplastin time; Quality assurance